الاتجاهات المعاصرة في العمارة واثرها علي الشكل المعماري (ولاية الخرطوم) - ا. أشرف صلاح الدين الطاهر الصديق; د. محمد علي أحمد جلي (White Nile Journal for Studies and Research, 2020)
Information age has a great impact on the speed of technological development, So that became part cannot be overlooked influence on architecture and architectural planning and contemporary trends, these technologies became an integral part of the architectural tools to formulate a thought in the design process, which was in the direction of smart buildings and smart cities. Technological development is a cornerstone of the development of societies and has a significant and effective impact on the development of architecture. Hence, the problem of the study arises as to where we are from this development. With the aim of finding the identity and the architectural and architectural character of the spirit of the times through the identification of the mechanisms and tools of contemporary architecture. To achieve the goal of the study was adopted in its theoretical framework to identify key vocabulary and the most accurate surround. And then fill out the questionnaire form that was distributed within the completion of the study requirements in order to draw the most important conclusions and final recommendations. The study concluded with a set of results related to the development of technology and its impact on local architecture, as well as the results of the analysis of the questionnaire ending with the general results. The most important recommendations were to narrow the digital divide between us and developed countries in terms of information technology and to expand the use of information technology. Through the use of the possibilities of technological developments in the ideas and works of the architectural designer as an active and teaching element in the movement of contemporary civilizational construction, these contemporary trends in architectural departments. And the need to adopt new design ideas based on the use of modern technological and digital systems and change in the construction of contemporary design thought of local architect